'Las ciencias curiosas': Curiosity, Studiousness and the New Philosophy in the Carta de Sor Filotea de la Cruz and the Respuesta a Sor Filotea de la Cruz. Issue 7 (July 2017) - Brooke, Alice
Abstract : This article analyses the presence of the discourse of curiosity in Manuel Fernández de Santa Cruz's Carta de Sor Filote a (1690) and Sor Juana's Respuesta a Sor Filotea (1691), an aspect of the texts that scholars have overlooked until now. It discusses the conflicting meanings each writer ascribes to 'curiosidad' and 'curioso', and how these engage with the changing understanding of the terms in the late seventeenth century. In doing so, it builds on Neil Kenny's research into early modern curiosity and, in particular, on the connection he identifies between curiosity and the nascent scientific method in the seventeenth century. This article argues that in addition to being one of the earliest texts in defence of women's learning in the Americas, the Carta and the Respuesta also present evidence for both the circulation of and the resistance to empirical ideas in late seventeenth-century New Spain.